ANALISIS SPASIAL PERSEBARAN MAHASISWA PROGRAM STUDI PPKN UNIVERSITAS PGRI SUMATERA BARAT BERDASARKAN ASAL DAERAH TAHUN 2020–2023 - Despica, Rika; Parwanida, Parwanida; Putra, Zandi (STKIP Pesisir Selatan, 2025)
One measure of a university's success is its ability to reach prospective students from diverse regions. Student distribution by region is a key indicator of a program's attractiveness and the effectiveness of promotion and recruitment. This article discusses the spatial analysis of the distribution of students in the Pancasila and Citizenship Education (PPKn) Study Program at the PGRI University of West Sumatra from 2020 to 2023. This study aims to identify student distribution patterns based on their region of origin and the factors that influence these choices. The method used in this study is a quantitative descriptive analysis with a GIS (Geographic Information System) approach to map the distribution of students. The results show that there is a tendency for student concentration from West Sumatra Province, dominated by the West Pasaman and Sijinjung areas. Meanwhile, from other provinces, the most consistent students come from Jambi Province, dominated by the Muaro Bungo and Teb areas. While Riau and Bengkulu provinces contribute little but participate every year, this has occurred a shift in distribution patterns over time. These findings are expected to provide insights for the development of student recruitment strategies and the development of study programs in the future.